The Ethical and Legal Standards of the Communicator in the Algerian Electronic press A descriptive study of the Executive decree 20-332 Electronic press - Barkati, Abdelnour (Journal of Legal Studies and Researches, 2023)
The study aims to stand on the set of ethical and legal standards brought by Executive Decree 20-332 on electronic journalism, in the era of technical transformations, whose performances were greatly reflected on professional and ethical, and created illegal and ethical manifestations, and the study concluded to criminalize fraudulent act and electronic hate speech, Controlling the behavior of workers in the digital field.